Anxiety as a mediator between perfectionism and eating disorders. - Egan, Sarah; Watson, Hunna; Kane, Robert; McEvoy, P.; Fursland, A.; Nathan, P. (Springer New York LLC, 2013)
There is a strong link between perfectionism and eating disorders, yet little research to date has examined mediators of this relationship. The aim of this study was to investigate the mediating effect of anxiety on the relationship between perfectionism and eating pathology in a clinical sample (N = 370, M age = 25.04, 99 % female) of treatment-seeking eating disorder patients (bulimia nervosa—41 %; eating disorder not otherwise specified—41 %; anorexia nervosa—18 %). Results from structural equation modeling indicated that anxiety partially mediated the relationship between self-oriented perfectionism and eating disorder psychopathology. The findings suggest the role of anxiety and perfectionism within cognitive-behavioral models of eating pathology, and have implications for the treatment of eating disorders.